A Scary Complication: Single-center Study on Management and Outcome of Cesarean Scar Pregnancy - Beate Hüner; Krisztian Lato; Frank Reister; Wolfgang Janni; Miriam Deniz (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract A cesarean scar pregnancy (CSP) is a scary and life-threatening complication of cesarean section (CS). Nevertheless, the incidence of CS is constantly growing. The CSP incidence is 0,15% of pregnancies after CS which represents 6,1% of all ectopic pregnancies in women with condition after CS. Therefore, it should be more present in the clinical daily routine. From mild nonspecific symptoms to hypovolemic shock, diagnosis and therapy must be performed quickly. With the progressive growth of the scar pregnancy, a uterine rupture involves the risk of severe bleeding, and an emergency hysterectomy could be necessary. Prolongation of pregnancy has been successful only in a few cases.We report 11 cases from our hospital in the past 10 years. In the discussion, treatment options of this complication with an increasing incidence, which is associated with serious morbidity and mortality, are presented based on the current literature. Treatment options include drug therapy, but also surgical or combined procedures with radiological intervention.